Annual Plan 1997-98 Volume-VII Hill Areas Government of Assam - Planning Commission (Planning Commission, 1997)
The target for 1997-98 have been set taking into account the feasibility and trend in production during last four years It is proposed to take up the following strategies during 1997-98. Effective measures of modern, technology to the farmer through extension programme, farmers training, group discussion, demonstration etc.
Government of Assam